The Mastery of Art Therapy in Working with Preschool Children - Zamelyuk, Maria I.; Mahdysiuk, Liudmyla I. (Mukachevo State University., 2021)
The study presents some aspects of art therapy in working with preschool children. The purpose of the study is to analyse the features of the creative activity of art therapy: game therapy, visual language, isotherapy, mandalas, collage; to reveal the characteristic features of the intervention of art in work with preschool children. The following general scientific methods were used to achieve this goal: analysis, synthesis, comparison, and modelling. It has been found that therapy helps children process difficult emotions, explore their "self", develop greater self-awareness and self-esteem, and learn to manage their emotions and solve problems. It has been studied that the creative process can help to work with memories, events and feelings that are identical to the emotions and activity of the child. It is substantiated that art therapy effectively helps children with anxiety, depression, trauma, and grief, and it can be used to increase the child's self-esteem, communication and problem-solving skills, socialisation. The necessity of using modern methods of art therapy is confirmed. The main aspects of working with preschool children are analysed. The practical side of using art therapy as an art for preschool children, tips and exercises that will help children get into the right way of thinking to create, which are included in any artistic activity to emphasise the therapeutic elements of the process. The current approaches to the art therapy process for preschool children are described: enhances creativity, allows children to express their thoughts and feelings, encourages the integration of psychological, physical and social aspects, improves productive functions, helps children make better decisions, helps children solve their problems, improves motility. The practical significance of the work is that it can be used by students, educators, psychologists, parents for in-depth study of art therapy in working with preschool children
Keywords: nonverbal communication; creativity; game therapy; visual language; isotherapy; mandalas; collage; 159.922.7-053.4:615.851